Transformation from Social Unity to a Quest for the Self: “Only Connect” In Forster’s Howards End And Smith’s On Beauty - Gulcu , Tarik Ziyad (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2020)
As the epitome of his humanistic view of life, E. M. Forster’s motto “only connect” is best represented by Howards End. Henry Wilcox’s and Margaret’s indifference and distanced approach to Leonard’s demand for employment because of his lower status, Helen’s failed efforts for the appreciation of the lower strata in the case of the Bast family and Leonard Bast’s acceptance of his inferiority to the Wilcoxes embody Forster’s anxieties regarding the “connection” among different social classes. However, contemporary man’s quest for a new self within the dynamism of the contemporary world despite the realisation of Forster’s emphasis on “connection” in the contemporary context is epitomised in Zadie Smith’s On Beauty. In the novel, Howard’s efforts for a new self by his affair with Victoria and his failure in returning to his family bonds indicate that Forster’s emphasis on “connection” among people turns into a quest for a new self in contemporary circumstances.